MULTICRITERIA ANALYSIS OF FLOOD CAUSES IN KUALA LUMPUR - Noordin, Nur Fazzillah; Abdullah, Alias; Shahbudin, Muhammad Nur Azraei (PLANNING MALAYSIA, 2007)
In today's world, natural disasters are becoming frequent occurrence as a result of human's excess and waste in using resources, especially land. Its effects can be seen in disasters such as flood in urban areas where population and built-up area is dense. Many studies have been conducted in flood prediction and river management but very few concentrate on evaluation of flood occurrence factors at rivers in urban areas. This study evaluates the significance of factors that cause urban flash floods in Kuala Lumpur by using Multi-Criteria Analysis (MCA) method with special reference to DEFINITE software. This study carries out a systematic approach encompassing a selection of criteria that determines the root cause of flood through consultation with major stakeholders like Department of Irrigation and Drainage (DID), Department of Environment (DOE), Kuala Lumpur City Hall (DBKL), and Malaysian Meteorological Department (MMD). Less than obvious results are due to the complexity and reality of the problem based on the interview of stakeholders with different views on the local environment. The MCA results reveal that stream and land (land use) are the main causes of flooding in urban areas that can be solved with a proper physical planning.